Exploring biochemical bases of resistance to fruit fly infestation in sweet gourd crops - Afroz, Mansura; Amin, Md Ruhul; Uddin Miah, Md Ramiz; Hossain, M Mofazzal; Sang, Jae Suh (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2021)
Female fruit flies, Bactrocera cucurbitae, thrust eggs into developing cucurbitaceous fruits, and larval feeding inside the fruits leads to damage. The biochemical properties of fruits can act against this insect pest. This study was carried out with 12 sweet gourd germplasm lines (Cucurbita moschata), namely BD 264, BD 265, BD 266, BD 268, BD 269, BD 274, BD 275, BD 277, BARI Mistikumra 1, BARI Mistikumra 2, Gazipur local line, and China line, to assess fruit fly abundance and infestation on germplasm lines, and to find out the relationship between the infestation of fruit flies and the biochemical properties of sweet gourd fruit. The lowest abundance of fruit flies was observed on BD 277, followed by BD 265, BD 264, and BD 275. The lowest number of maggots was found in BD 274, followed by BD 264, and BD 277. In terms of fruit infestation, BD 274 and BD 277 were identified as resistant lines; BD 264, BD 265, BD 266, BD 268, BD 269, and BD 275 were classified as moderately resistant lines; and BARI Mistikumra 1, BARI Mistikumra 2, Gazipur local line, and China line were categorized as susceptible lines. The biochemical properties of the germplasm lines varied significantly. The infestation of fruit fly had significant positive correlation with the moisture content of BD 266, BARI Mistikumra 1 and BARI Mistikumra 2, and the reducing sugar content of BARI Mistikumra 1 and BARI Mistikumra 2.